Sport, space and segregation Pietermaritzburg, 1900-1980 - Merrett, Christopher (Department of Historical Studies, 2023)
Sport is located historically within its political, economic, cultural and social context in order to assess its role in human and spatial relations; and its meaning for various communities. This study aims to measure the impact of dominant ideology (imperialism, segregation and apartheid), the degree to which sport was used instrumentally by the authorities, and the extent to which it was seen as a site of struggle by the oppressed. The main sources for this thesis were archival and published material emanating from the municipality. Before apartheid matured and became more secretive, they were remarkably candid about official aims and objectives. A wide variety of secondary sources was consulted; and interviews conducted. The conclusion is that sport is an appropriate lens through which to view urban history and the relationships that shape it. Driven by a consistent ideological desire for White separateness, sport reflected social hegemony and assumptions about relative competence and ability. Instrumental use of sport by the local authority, apart from a skewed use of economic resources to unite whites and maintain their distance from other communities, was poorly regarded. This was because of the availability of other, coercive means of control and the dispensability of the individuals targeted. Black sportspersons were in effect squatters at impermanent facilities. Black recreation was a challenge to White ideas about the use of urban space. For Africans, the controlled area preferred by the authorities was the beerhall, not the sports field. Effective resistance organised around sport emerged only when the authorities needed Asian and Coloured cooperation to implement group areas and at this point sport became a notable site of struggle. Ultimately sports facilities, originally a symbol of White civilisation and authority, became a potent emblem of the spatial conflict that characterised apartheid. They also reflected the fact that South African urban geography had always been an evolving saga of insiders and outsiders. Sport provided the proponents of White dominance with a theatre for propaganda; while at the same time offering its protagonists a stage upon which to demonstrate their opposition. In this scenario hegemony was in a state of periodic flux. For a more descriptive abstract of this thesis, see the section 'Final overview' on pages 353-356.